Transnational Students and Quality in Education System in the Tijuana-San Diego Region - Osuna García, José Candelario (2019)
The Tijuana-San Diego region is the most important binational area on the border between Mexico and the United States, because of the dynamism and observed social-economic interaction, with a high rate of urban growth, a strong interaction of capital flows, workers and goods, which promote the economic and demographic expansion of the same region (Alegría, 2010). However, the relationship between the two countries is also characterized by sharing groups of students that attend two education systems with profound inequalities in regards to the quality of education, infrastructure, and learning. Situations that represent significant challenges in terms of cross-border planning (Guillén López, 1993). In this region, the educational problem of transnational students and the inequality in knowledge and demonstration of universal learning are two pedagogical phenomena that crystallize the urgent need to eliminate the border barriers between Mexico and the United States to carry out actions jointly and find a solution. Therefore, the objective of this academic text is to describe the current landscape of the quality of learning in the school systems of California and Baja California, by comparing the results achieved in large-scale international evaluations, to identify the implications of this educational horizon for the adaptation of transnational students.